Odpowiedź :
Odpowiedź:
1.
a) 7 - 10 = - 3
12 - 18 = - 6
35 - 60 = - 25
18 - 26 = - 8
b) (-5) - 4 = (- 9)
(-7) - 12 = (- 19)
(-13) - 22 = (- 35)
(-50) - 33 = (- 83)
c) 6 - (-9) = 6 + 9 = 15
(-4) - (-7) = (-4) + 7 = 3
(-8) - (-3) = (-8) + 3 = (- 5)
(-15) - (-12) = (-15) + 12 = (-3)
2.
a)( -1) - 9 = (- 10)
(-5) - 9 = (- 14)
1 - 9 = (-8)
3 - 9 = (-6)
(-9) - 9 = (-18)
9 - 9 = 0
17 - 9 = 8
b) 7 - (-12) = 7 +12 = 19
12 - (-12) = 12 + 12 = 24
0 - (-12) = 0 + 12 = 12
(-6) - (-12) = (-6) + 12 = 6
(-10) - (-12) = (-10) + 12 = 2
(-20) - (-12) = (-20) + 12 = (-8)
(-35) - (-12) = (-35) + 12 = (-23)
Odpowiedź:
Szczegółowe wyjaśnienie:
7-10= -3
-5-4= -9
6-(-9)=6+99=15
12-18 = -6
-7 -12= -19
-4-(-7)=-4+7=3
35-60= -25
-13-22= -55
- 8-(-33)=-8+33=25
18-26=-8
-50 -33=-88
-15 -(-12)= -15+12= -3
__________________________
-1-9=-10
-5-9=-14
1- 9=-8
3 -9=-6
-9-9=-18
9-9=0
17-9=8
_________________
7-(-12)=7+12=19
12-(-12)=12+12=24
0- (-12)=0+12=12
-6 -(-12)=-6+12=6
-10-(-12)=-10+12=2
-20 -(-12)=-20+12= -8
-35- (-12)=-35+12= -23